2013 IEEE International Conference on Mechatronics and Automation 2013
DOI: 10.1109/icma.2013.6618124
|View full text |Cite
|
Sign up to set email alerts
|

Finger joint continuous interpretation based on sEMG signals and muscular model

Abstract: The human hand is very dexterous and can perform various of gestures in activities of daily living. Only dividing the motions of hand into several types and applying pattern recognition method for implementation of manipulation control may result in low dexterity and delicacy. In this paper, a novel finger joint interpretation method based on sEMG signals and muscular model is presented. The motion of finger is flexion and extension without any external resistant force and at a natural movement velocity. sEMG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The Kalman filter estimates the current state based on the state of the last moment and estimates the optimal state through the correction of the estimated state and the observed state at the current moment, to obtain the optimal solution and realize the correction of the whole prediction process. Ang et al ( Pang et al, 2013 ) used the Kalman filter to process surface EMG signals and conducted experiments on five subjects. The results showed that the designed Hill muscle model could predict the angle of fingers when they naturally bent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kalman filter estimates the current state based on the state of the last moment and estimates the optimal state through the correction of the estimated state and the observed state at the current moment, to obtain the optimal solution and realize the correction of the whole prediction process. Ang et al ( Pang et al, 2013 ) used the Kalman filter to process surface EMG signals and conducted experiments on five subjects. The results showed that the designed Hill muscle model could predict the angle of fingers when they naturally bent.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a relationship model between sEMG features and the upper limb movement angle was set up. The participants in different trials vary from 5 to 20 according to the studies in ( Pang et al, 2013 ; Geng et al, 2016 ; Wu and Chen 2021 ). The number of subjects in this trial was eight (including seven males, one female), aging between 23 and 32 years old, and six right-hands and two left-hands were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of Electromyography technology, this biological signal detected from contracting muscle has been widely used in biorobots control [1]- [3], body motion recognition [4]- [5], rehabilitation [6] and athlete training. The essential characteristic of EMG signal makes it very convenient and direct to represent status of skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%
“…INCE the discovery of electromyograms signal in 1666, it has been implemented in many kinds of fields, such as biorobots control [1]- [7], human body motion recognition [8]- [10], rehabilitation [12]- [13] and so on. Comparing with the other signals detected from conventional sensors, such as force sensor and acceleration sensor, EMG signals can reflect the intention of human motion and the electrode which is used to detect EMG signals is relevant small.…”
Section: Introductionmentioning
confidence: 99%